"The effects of non-surgical periodontal treatment plus zinc and magnesium supplementation on oxidative stress and antioxidants enzymes in type 2 diabetes patients: a quasi-experimental study" - José Carlos Alarcón-Moreno; Mónica Flores-Muñoz; María Sobeida L. Blázquez-Morales; Miguel Eric García-Rivera; Juan Carlos Rodríguez-Alba; Claudio Rafael Castro-López; Francisco Javier Nachón-García; Víctor Hugo Muñoz-Muñoz; María Gabriela. Nachón-García (BMC, 2024)
Abstract Background Periodontal Disease (PD) associated with Type 2 Diabetes Mellitus (T2DM) is a chronic condition that affects the oral cavity of people living with T2DM. The mechanisms of the interaction between type 2 Diabetes Mellitus and Periodontal diseases are complex and involve multiple pathophysiological pathways related to the systemic inflammatory process and oxidative stress. Non-surgical periodontal treatment (NSTP) is considered the standard for the management of this disease; however, patients with systemic conditions such as type 2 Diabetes Mellitus do not seem to respond adequately. For this reason, the use of complementary treatments has been suggested to support non-surgical periodontal treatment to reduce the clinical consequences of the disease and improve the systemic conditions of the patient. The use of zinc gluconate and magnesium oxide as an adjunct to non-surgical periodontal treatment and its effects on periodontal clinical features and oxidative stress in patients with Periodontal diseases -type 2 Diabetes Mellitus is poorly understood. Methods A quasi-experimental study was performed in patients with periodontal diseases associated with T2DM. Initially, 45 subjects who met the selection criteria were included. 19 were assigned to a control group [non-surgical periodontal treatment] and 20 to the experimental group (non-surgical periodontal treatment + 500 mg of magnesium oxide and 50 mg of zinc gluconate for oral supplementation for 30 days) and the data of 6 patients were eliminated. Sociodemographic characteristics, physiological factors, biochemical parameters, and clinical features of periodontal diseases were assessed. Results In this research a change in periodontal clinical characteristics was observed, which has been associated with disease remission. Additionally, a shift in MDA levels was presented for both groups. Furthermore, the supplementation group showed an increase in antioxidant enzymes when compared to the group that only received NSPT. Conclusion The use of Zinc gluconate and magnesium oxide can serve as a complementary treatment to non-surgical periodontal treatment, that supports the remission of PD as a result of regulation-reduction of oxidative biomarkers and increase in antioxidant enzymes activity. Trial Registration https://www.isrctn.com ISRCTN 14,092,381. September 13º 2023. Retrospective Registration. Graphical Abstract